2015
DOI: 10.3727/096368915x686841
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cells: A New Era for Stem Cell Therapy

Abstract: The human umbilical cord is a promising source of mesenchymal stem cells (HUCMSCs). Unlike bone marrow stem cells, HUCMSCs have a painless collection procedure and faster self-renewal properties. Different derivation protocols may provide different amounts and populations of stem cells. Stem cell populations have also been reported in other compartments of the umbilical cord, such as the cord lining, perivascular tissue, and Wharton's jelly. HUCMSCs are noncontroversial sources compared to embryonic stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
350
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(359 citation statements)
references
References 75 publications
(108 reference statements)
5
350
0
4
Order By: Relevance
“…The authors suggested that MSC plasticity was linked with the expression of early differentiation markers. MSCs from various sources are able to differ entiate not only in mesoderm lineages, but into ecto derm and endoderm derivatives (Huang et al, 2010;Antonucci et al, 2011;Mamidi et al, 2011;Ding et al, 2015). It has been demonstrated that human bone marrow MSCs expressed biologically active compounds that modified the microenvironment in the damaged tissue and facilitated tissue repair (Caplan, Dennis, 2006;Phinney, 2007;Tan et al, 2011).…”
Section: Surface Marker Expression In Fetmsc and Fetmsc And Their Sphmentioning
confidence: 98%
“…The authors suggested that MSC plasticity was linked with the expression of early differentiation markers. MSCs from various sources are able to differ entiate not only in mesoderm lineages, but into ecto derm and endoderm derivatives (Huang et al, 2010;Antonucci et al, 2011;Mamidi et al, 2011;Ding et al, 2015). It has been demonstrated that human bone marrow MSCs expressed biologically active compounds that modified the microenvironment in the damaged tissue and facilitated tissue repair (Caplan, Dennis, 2006;Phinney, 2007;Tan et al, 2011).…”
Section: Surface Marker Expression In Fetmsc and Fetmsc And Their Sphmentioning
confidence: 98%
“…Regarding their therapeutic value, storage banking system and protocols should be established immediately. Ding et al [18]. critically evaluates their therapeutic value, challenges, and future directions for their clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…15 WJ-MSC secrete large amounts of cytokines, and are non-oncogenic; thus, they are an ideal source of MSC for cell therapies. 16,17 WJ-MSC play a role in immune regulation through direct contact or secretion of cytokines. 18 However, the application of WJ-MSC in spontaneous abortion has not been reported.…”
mentioning
confidence: 99%